1-Quasiconformal Mappings and CR Mappings on Goursat Groups - Wu, Qing Yan (Hindawi Publishing Corporation, 2014)
We show that 1-quasiconformal mappings on Goursat groups are CR or anti-CR mappings. This can reduce the determination of 1-quasiconformal mappings to the determination of CR automorphisms of CR manifolds, which is a fundamental problem in the theory of several complex variables.